Research on the change of the storage volume of the Nordic Seas Overflows over the last 40 years - Wenqi Shi; Minjie Xu; Xianqing Lv; Xianqing Lv (Frontiers in Marine Science, 2024)
The Nordic Sea overflow, being a significant driver of the thermohaline circulation, exerts a substantial influence on environmental dynamics in the Arctic and globally. A better understanding about the trend of the storage volume of the Nordic Seas Overflows is of paramount importance to a realistic assessment of the North Atlantic circulation and variability. EN4.2.2 reanalysis data were utilized to acquire the monthly average time series of overflow water storage volume in the Nordic Sea from 1950 to 2022. The storage volume demonstrates seasonal variations, with fluctuations of approximately 10% around the average. Over the period from 1980 to 2022, the average volume per decade exhibited a consistent decrease. Linear fitting of the annual average data estimated the overall relative change trend in the last 43 years to be -7.2 ± 2.6%. However, the quality of the EN4.2.2 data brings the average error of about 12% in the calculation of the overflow storage volume, which implies that the downward trend requires further validation. From a spatial standpoint, the Norwegian Sea, particularly the Lofoten Basin, is the primary region where overflow water storage volume in the Nordic seas have decreased. This decrease corresponds to an increase in ocean temperatures within the upper layer (0-600m) of both the Lofoten Basin and the Norwegian Basin. The warming of these regions has directly impacted the overflow water storage volume, leading to its reduction. It is noteworthy that the ocean temperature rise in the upper layer is more influenced by the Atlantic inflow rather than air-sea flux, particularly in the Norwegian Basin. This is attributed to the substantial increase in SST in the North Atlantic, which aligns with the warm current regions in the Atlantic Ocean, and the lack of statistical significance in linear trend of the air-sea heat flux. Furthermore, there has been a more rapid reduction in the overflow storage volume in the Norwegian Sea from 2011 to 2022. Specifically, the annual average overflow volume from 2018 to 2022 dropped below the previous lowest value. Concurrently, the salinity of the upper Norwegian Sea and the Atlantic inflow decreased considerably, while there has been no significant change in ocean temperature. Therefore, this short-term fluctuation is predominantly attributed to the decrease in Atlantic inflow salinity. Interestingly, the decrease in overflow water volume in the Nordic Seas does not follow a linear pattern in relation to increasing ocean temperature; instead, it exhibits an accelerating trend. If the ocean temperature rises by 1°C, the overflow water volume in the Nordic Seas will decrease to 86% of the total volume. Overall, the overflow water storage in the Norwegian Sea undergoes complex interannual variations and is notably influenced by the influx from the Atlantic Ocean.